Taxonomic diversity and toxicological assessment of Cyanobacteria in Moroccan inland waters - Douma, Mountasser; Loudiki, Mohammed; Oudra, Brahim; Mouhri, Khadija; Ouahid, Youness; del Campo, Francisca (Revue des sciences de l'eau / Journal of Water Science, 2009)
AbstractResearch on the ecology, biodiversity and toxicology of cyanobacteria in Moroccan inland waters has been carried out since 1994. The results demonstrate the existence of several taxa of cyanobacteria. Most of them are toxic, bloom‑forming species present in various water bodies of the country. The present study follows upon this earlier work and spans the 2003-2006 period. The major aim was to update and supplement the existing national cyanobacteria inventory and to isolate new toxic strains. During the study period, more than 40 aquatic environments were visited and sampled.Almost 300 taxa of cyanobacteria were recorded. They belonged to 3 orders, 14 families and 46 genera. Among these, about 78 taxa are recorded for the first time in Morocco; 29 strains of cyanobacteria were successfully isolated and cultured in the laboratory. All the collected cyanobacteria, including natural blooms, mats, and cultured strains, were analyzed for toxicity and hepatotoxins (microcystins) were quantified. Using the High-performance liquid chromatography technique coupled to photodiode array (PDA) detector (HPLC-PDA), four samples of Microcystis blooms showed the presence of microcystins (MCs), with a concentration ranging between 1.87 and 64.4 µg•g‑1 MC‑LR eq (microcystin-LR equivalents). A total of five different structural variants of MCs were detected (MC-LR, -RR, -YR, -FR, -WR). Furthermore, 3 of 29 isolates were confirmed as MCs producing strains.The results show that the widening of the survey led to a better knowledge of the diversity of cyanobacteria. The taxonomic inventory was greatly increased and several cyanobacteria strains were characterized for their toxicity. The results should be useful as a database for the identification of various aquatic environments contaminated by cyanobacterial toxins (microcystins), which represent a potent sanitary risk for human and animals.